Characterization of nanoparticles in aerosolized photocatalytic and regular cement. Issue 5 (4th May 2019) - Batsungnoen, Kiattisak; Hopf, Nancy B.; Suárez, Guillaume; Riediker, Michael
Abstract: Photocatalytic cement containing nano-TiO2 has been introduced to the construction industry because of its biocidal and self-cleaning properties. Although, TiO2 is classified as possibly carcinogenic to humans, the cancer risk among cement workers is currently unknown. This is partly because an assessment of exposures to airborne photocatalytic cement is missing. We characterized airborne photocatalytic cement in an experimental aerosolization set-up and compared it to regular cement. Aerosolized nanoparticle size distributions and concentrations were measured with a scanning mobility particle sizer (SMPS) and a portable aerosol spectrometer (PAS). Particle morphology was analyzed with a scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Energy dispersive X-ray analysis (SEM-EDX) was used for elemental determination. The aerosolized photocatalytic cement powder contained 5% nanosized particles in number concentration while regular cement had only a negligible amount. Airborne photocatalytic cement concentration was 14, 900 particles per cubic centimeter (pt/cm 3 ) with a geometric mean diameter (GMD) of 249 nm (geometric standard deviation; GSD ±2 nm). Airborne regular cement concentration and GMD (GSD) were 9, 700 pt/cm 3 and 417 nm (±2 nm), respectively. Photocatalytic cement contained 18.5 times more airborne nano-TiO2 (37%) compare to bagged powder (2%). Aerosolized photocatalytic cement had a significantly smaller particle size distribution and greater particle concentration compared to regular cement. Both types of cement had 99% of the particles with sizes less than 1  μ m. Nano-TiO2 was directly aerosolized from the cement, followed with a coagulation/agglomeration process. Future studies should evaluate workers' exposures associated with the use of photocatalytic cement. Copyright © 2019 American Association for Aerosol Research